Structure and mechanical characteristics of the hypereutectic silumin subjected to pulsed electron beam treatment; IOP Conference Series: Materials Science and Engineering; Vol. 597 : Prospects of Fundamental Sciences Development (PFSD-2019) - Petrikova E. A.; Teresov A. D.; Rygina (Gracheva) M. E. Mariya Evgenjevna; Ivanov Yu. F. Yuriy Fedorovich (2019, 2019)
Title screen